Pilkada, Aspek Edukasi, dan Nilai-Nilai Demokrasi di Kalangan Mahasiswa UNM - Subair, Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the participation of Makassar State University (UNM) students in the Pilkada and expand the extent to which aspects of political education and understanding of democratic values ​​are applied among students. Using a quantitative descriptive survey method, data was collected from 385 respondents selected through simple random sampling techniques. The research results show that 62% of UNM students participated in the Pilkada, but most relied on information from social media rather than formal education on campus. The political education received on campus is still deemed to be less relevant in preparing students for regional elections, even though most students understand the basic concepts of democracy. A positive correlation of 0.62 was found between the quality of political education and the implementation of democratic values ​​such as freedom of expression and equality. This research concludes that increasing student participation in regional elections can be achieved through improvements in political education approaches on campus. More contextual and practical education can strengthen the understanding and implementation of democratic values ​​among students, so that they are better prepared to play an active role in the democratic process. It is hoped that the results of this research can become a reference in developing political education programs in higher education environments